FINANCING DISTRIBUTION, FINANCING TO DEPOSIT RATIO (FDR) AND NON PERFORMING FINANCING (NPF) ON PROFITABILITY OF THE ISLAMIC RURAL BANKS IN BANTEN PROVINCE - Nailul Mubarokah; Umiyati Umiyati (Sekolah Tinggi Ekonomi Islam (STEI) SEBI, 2020)
This study aims to determine empirical evidence about the effect of profit sharing financing, sale and purchase financing, FDR and NPF on the profitability (ROA) of Islamic Rural Banks (BPRS) in Banten Province. The type of data in this study is secondary data using panel data. The research object was five Islamic Rural Banks in Banten Province and research period from the first quarter to the fourth quarter of 2013-2019. The research sample was selected using purposive sampling technique. The analysis method used is Panel Data Regression Analysis with Eviews 10 software. The results obtained in this study indicate that there is no significant influence between the Profit Sharing variable on Profitability (ROA) partially. Sale and Purchase Financing, FDR, and NPF variables partially have a significant effect on profitability (ROA). Simultaneously, Profit Sharing, Sale and Purchase Financing, FDR, and NPF have a significant effect on Profitability (ROA).